An Investigation of ChatGPT Application of Faithful Translation in Rendering Figurative Language from English to Indonesian - Jayanthi, Komang Ayu Manik Trisna; Jayantini, I Gusti Agung Sri Rwa (Udayana University, 2026)
This study investigated the faithful translation features of ChatGPT in translating figurative language from English to Indonesian, using Newmark’s (1988) faithful translation theory. It applied a qualitative descriptive method by inputting selected lyric lines into ChatGPT and comparing the outputs closely with the source text. The data were taken from Taylor Swift’s song “You’re Losing Me” and classified into metaphors, hyperboles, and ironies. Each translation was assessed based on how well it preserved contextual meaning, imagery, and stylistic effect while still sounding natural in Indonesian. The findings show that ChatGPT often produced translations aligned with faithful translation principles, especially when expressions were culturally transferable. However, it showed limitations in rendering culturally embedded or emotionally expressions. Overall, ChatGPT can function as a useful preliminary tool, but post-editing and collaboration with human translators remain essential to ensure accuracy, tone, and interpretive depth.